Uso de reguladores vegetais na germinação das sementes de citrumelo 'Swingle' - Liberato, Érica Maria Sauer [UNESP]; Leonel, Sarita [UNESP]; Modesto, Joyce Helena [UNESP]; Souza, Jackyson Myrellis Azevedo [UNESP]; Gonçalves, Bruno Henrique Leite [UNESP] (My University, 2013)
The citrumeleiro ' Swingle ' is of great importance for the Brazilian citrus rootstock. The purpose of this study was to evaluate the effect of the use of different plant regulator on seed germination of ' Swingle citrumelo '. For evaluation of germination were used different doses of gibberellic acid (0, 25, 50, 75 and 100 mg.L-1 ) and biostimulant Stimulate ™ (0, 100, 150 and 200 mL L-1 ). After the beginning of the germinative process evaluations were performed daily until the thirty-fourth (34th) day. through the statistical analysis of the results obtained, it was possible to conclude that the fruits of citrumelo ' Swingle feature good uniformity and that the use of gibberellic acid is promising for commercial use with this rootstock.

O citrumeleiro ‘Swingle’ é de grande importância para a citricultura brasileira como porta- enxerto. O objetivo do presente trabalho foi avaliar o efeito do uso de diferentes reguladores vegetais na germinação de sementes de citrumelo ‘Swingle’. Para avaliação da germinação foram utilizadas diferentes doses de ácido giberélico (0, 25, 50, 75 e 100 mg.L-1 ) e do bioestimulante Stimulate™ (0, 100, 150 e 200 mL.L-1 ). Após o inicio do processo germinativo, as avaliações foram realizadas diariamente até o trigésimo quarto (34º) dia. Através da análise estatística dos resultados obtidos, foi possível concluir que os frutos de citrumelo ‘Swingle’ apresentam boa uniformidade e que o uso de ácido giberélico é promissor para uso comercial com esse porta-enxerto.
Effect of the use of plant regulators on seed germination of 'Swinglecitrumelo'
Keywords: Poncirustrifoliata x Citrus paradise; Bioregulators; Biostimulant; Poncirustrifoliata x Citrusparadisi; Biorreguladores; Bioestimulante